Correction: Mateusz, S., et al. Iron Supplementation in Suckling Piglets: An Ostensibly Easy Therapy of Neonatal Iron Deficiency Anemia. Pharmaceuticals 2018, 11, 128 - Mateusz Szudzik; Rafał R. Starzyński; Aneta Jończy; Rafał Mazgaj; Małgorzata Lenartowicz; Paweł Lipiński (MDPI AG, 2019)
The authors wish to make the following corrections to this paper [1]: the term "liposomal" should be replaced with the term "sucrosomial" in the following places [...]